Empowering Language Assessment: The Pioneering Role Of Artificial Intelligence - Nurus Sufiyah Lailatul Hidayah; Faidatuz Zahroini Hasyim; Vira Yunita (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The integration of Artificial Intelligence (AI) in language assessment has revolutionized the field, offering innovative solutions to longstanding challenges. This paper explores the transformative impact of AI in language assessment, emphasizing its pioneering role in enhancing accuracy, efficiency, and inclusivity. Through an extensive literature review, this study analyzes various AI-based language assessment methodologies, including automated essay scoring, speech recognition, natural language processing, and adaptive testing. By examining the strengths and limitations of each approach, we unravel the capabilities of AI in tailoring assessments to individual learners' needs, providing personalized and constructive feedback.